Crescimento inicial e respostas fisiológicas de genótipos de capim-elefante sob estress hídrico em comparação à cana-de-açúcar. - Santos, Jhulyanne Christiny Marcelino dos (2019)
Elephant grass (Pennisetum pururem Schum.) And sugarcane (Saccharum spp.) Are species with high biomass production potential for bioenergy, and elephantgrass can develop on nutrient-poor soils, making it possible to use marginal areas to traditional agriculture. However, one of the difficulties in using elephantgrass is its low tolerance to long periods of drought, which are very common in semi-arid areas of Northeastern Brazil. The objective of this work was to compare the initial growth of elephant grass and sugarcane RB92579 and its physiological characteristics regarding tolerance or susceptibility to water deficit conditions. The experiment was conducted in a greenhouse of the Agricultural Sciences Center of the Federal University of Alagoas. The experimental design was a randomized complete block design in a 5x2 factorial scheme, with four elephantgrass genotypes (BRS Capiaçu cultivar and 3 Madeira, Venezuela and Pasto Panama clones) and one sugarcane (RB92579). and two levels of water available in the soil distributed in six blocks having one repetition per block, totaling 60 experimental plots. Each plot was composed of a pot containing 100 kg of soil in which a plant was planted. The water regimes were: control treatment (> 80% of available water in the soil - AD), and stress (total suspension of irrigation). The plants had their growth accompanied up to 68 days after the planting, being evaluated the morphological characteristics: plant height, number of leaves, stem diameter, leaf area. After this period, the implantation of the water treatments with total suspension of irrigation began. When the plants reached maximum stress, they were rehydrated. (Photosynthesis, stomatal conductance, transpiration and internal carbon dioxide concentration) and the maximum photochemical efficiency of photosystem II (Fv / Fm) and the effective quantum efficiency of PSII (ΦPSII) . In general, elephantgrass genotypes presented similar vegetative growth behavior in most of their morphological characteristics, although the genotype Pasto panamá showed higher plant height, Venezuela had a longer leaf length +3 and BRS Capiaçu had the highest number of plants tiller. The elephantgrass genotypes showed higher initial growth than sugarcane, presenting higher numbers of leaves and tillers, stem diameter, plant height and leaf area, resulting in a greater accumulation of sugarcane biomass 68 days after planting. The genotypes Pasto Panama and Venezuela have physiological characteristics of greater susceptibility to drought. The strategies triggered by the BRS Capiaçu genotype, such as lower reductions in relative leaf water content, stomatal conductance, transpiration, photosynthesis and effective photochemical efficiency in water stress conditions, provide better drought tolerance.